Development and optimization of a high‐throughput screening assay for in vitro anti‐SARS‐CoV‐2 activity: Evaluation of 5676 Phase 1 Passed Structures. Issue 7 (23rd March 2022) - Chiu, Winston; Verschueren, Lore; Van den Eynde, Christel; Buyck, Christophe; De Meyer, Sandra; Jochmans, Dirk; Bojkova, Denisa; Ciesek, Sandra; Cinatl, Jindrich; De Jonghe, Steven; Leyssen, Pieter; Neyts, Johan; et al.
Abstract: Although vaccines are currently used to control the coronavirus disease 2019 (COVID‐19) pandemic, treatment options are urgently needed for those who cannot be vaccinated and for future outbreaks involving new severe acute respiratory syndrome coronavirus virus 2 (SARS‐CoV‐2) strains or coronaviruses not covered by current vaccines. Thus far, few existing antivirals are known to be effective against SARS‐CoV‐2 and clinically successful against COVID‐19. As part of an immediate response to the COVID‐19 pandemic, a high‐throughput, high content imaging–based SARS‐CoV‐2 infection assay was developed in VeroE6 African green monkey kidney epithelial cells expressing a stable enhanced green fluorescent protein (VeroE6‐eGFP cells) and was used to screen a library of 5676 compounds that passed Phase 1 clinical trials. Eight drugs (nelfinavir, RG‐12915, itraconazole, chloroquine, hydroxychloroquine, sematilide, remdesivir, and doxorubicin) were identified as inhibitors of in vitro anti–SARS‐CoV‐2 activity in VeroE6‐eGFP and/or Caco‐2 cell lines. However, apart from remdesivir, toxicity and pharmacokinetic data did not support further clinical development of these compounds for COVID‐19 treatment.